Synthesis of psoralen analogues based on dibenzofuran - Campos, Ana M. F. Oliveira (2003)
The syntheses of four novel psoralen derivatives, 6a-d, of the benzofurocoumarin (=benzofuro[1]benzopyranone) type containing an ester group are described. These compounds might be of interest in PUVA (psoralen long-wave ultraviolet radiation) therapy. The overall efficiency of the synthetic procedure is greatly limited by the low yields for the penultimate step, i.e. formylation of the dibenzofuranols 3a,c or protected dibenzofuranol 4d to the carboxaldehydes 5 (Scheme 4). However, the final stage to form the pyranone ring from 5a-d proceeds smoothly (Scheme 5).